Towards an Integrated Orobanche Management: Understanding Farmers’ Decision-Making Processes Using a Discrete Choice Experiment - Ahmed Yangui; Taheni Mlayeh; Zouhaier Abbes; Mohamed Kharrat (Agronomy)
Controlling the Orobanche weed parasite is a major challenge for farmers, and the individual application of various management practices has not yet proven to be successful in addressing this issue. To develop an effective strategy for managing this parasitic weed, an Integrated Orobanche Management (IOM) approach has become a priority. Using a Discrete Choice Experiment (DCE) methodology, we analyze the trade-off in farmers’ preferences between different attributes of IOM scenarios and estimate their willingness to pay (WTP). A sample of 124 Tunisian faba bean farmers participated in the study. The findings indicate that Tunisian farmers are open to adopt an IOM that includes Orobanche-tolerant faba bean varieties, and that the cost of technical package does not seem to be an obstacle. Nevertheless, farmers feel to be rewarded for delaying the sowing date from November to December. Furthermore, the study highlights that farmers show no clear preferences for the use of herbicide, specifically glyphosate, as well as for the practice of intercropping with fenugreek. While increasing faba bean yields remains a priority, farmers are willing to pay more for IOM scenarios that reduce the Orobanche plant shoot count. In conclusion, there is significant heterogeneity in farmers’ preferences, their financial situation, and the severity of Orobanche infestation significantly influencing their decision. Policy recommendations are derived from our results.